Post‐acquisition financial performance and executive compensation - Schmidt, Dennis; Fowler, Karen L. (Strategic Management Journal, 1990)
Abstract This study reports the results of an empirical analysis of post‐acquisition financial performance and changes in executive compensation. A model of the determinants of cash compensation is presented and tested. Firm size, form of acquisition, executive motivation, and financial performance are analyzed for two groups of acquiring firms. Results are compared to a group of non‐acquiring firms. The financial performance measures include accounting and capital market data for a 4‐year period both preceding and following acquisition activity. The results indicate that, on average, firms which engaged in a major acquisition performed poorly in the post‐acquisition period. Top executives of those firms, on average, experienced significant increases in cash compensation. After controlling for size effects, financial performance related strongly to changes in executive compensation for the non‐acquiring firms, but generally did not relate to changes in executive compensation for the acquiring firms.